2020
DOI: 10.1186/s13019-020-1058-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac surgery in acute myocardial infarction: crystalloid versus blood cardioplegia – an experimental study

Abstract: Background: Because hearts in acute myocardial infarction are often prone to ischemia-reperfusion damage during cardiac surgery, we investigated the influence of intracellular crystalloid cardioplegia solution (CCP) and extracellular blood cardioplegia solution (BCP) on cardiac function, metabolism, and infarct size in a rat heart model of myocardial infarction. Methods: Following euthanasia, the hearts of 50 rats were quickly excised, cannulated, and inserted into a blood-perfused isolated heart apparatus. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In a recent experimental model of infarcted myocardium, blood cardioplegia provided better recovery than crystalloid cardioplegia. 20 We support the thesis that superiority of one solution over another may be observed in a particular clinical situation or particular cohort of patients.…”
Section: Discussionsupporting
confidence: 75%
“…In a recent experimental model of infarcted myocardium, blood cardioplegia provided better recovery than crystalloid cardioplegia. 20 We support the thesis that superiority of one solution over another may be observed in a particular clinical situation or particular cohort of patients.…”
Section: Discussionsupporting
confidence: 75%
“…Cardiac surgery inevitably leads to ischemia/reperfusion (I/R) injury, potentially causing postoperative myocardial dysfunction, such as pulmonary dysfunction, atrial brillation, and renal failure(8). Currently, there are two primary categories of cardiac arrest solutions: one containing high levels of potassium, magnesium, and bicarbonate in the extracellular uid, and the other containing electrolyte components in the intracellular uid (4,9). The use of cardioplegia not only stops the heart but also reduces ischemia/reperfusion damage and improves immediate or long-lasting results (10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Blood intrinsically possessed buffer capacity that might curtail myocardial swelling, alongside its function of oxygen transport, enabling rapid induction of arrest under oxygenated conditions. Conversely, the HTK solution-a sodium-de cient intracellular-type cardioplegic mediumelicited functionality through the reduction of extracellular sodium levels, and had garnered clinical recognition for e cacious organ preservation (4). Its broad adoption rested on its single-administration protocol, ensuring extended myocardial safeguarding exceeding two hours of cardiac asystole.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that perioperative CI and postoperative percent fractional shortening were significantly higher in the HTK group. On the other hand, in an experimental model of acute MI, Boening et al 26 noted that the application of Buckberg blood cardioplegia leads to better myocardial recovery than HTK after 90 minutes of cross-clamping. Gaudino et al 27 revealed that single dose HTK solution causes inferior RV protection compared with warm blood cardioplegia in patients with depressed preoperative RV function after mitral valve surgery.…”
Section: Discussionmentioning
confidence: 99%